For Your Eyes Only: A Field Experiment on Nudging Hygienic Behavior - Mobekk, Hilde; Hessen, Dag Olav; Fagerstrøm, Asle; Jacobsen, Hanne (Frontiers in Psychology, 2020)
These days many gyms and fitness centers are closed to reduce transmission of the SARS-CoV-2 virus in society. The gym is an environment rich in microorganisms, and careful hygiene is a necessity to keep infections at bay. Exercise centers strive for better hygiene compliance amongst their members. This effort has become essential in light of the current pandemics. Several experimental studies show that others' physical presence, or the "illusion" of being watched, may alter behavior. This article reports on a natural field experiment testing one specific social nudge intended to increase gym members' hygienic behavior. The study was conducted before the SARS-COV-2 pandemic. A picture of "observing eyes" was attached to paper dispensers and cleanser spray bottles at two different gyms in Norway. A reversal design, also called an ABA design, with and without the nudge's presence, was used to investigate the impact on gym members' hygienic behavior. A follow-up study was conducted in one of the centers to investigate whether the nudge stimuli would function over time. The study included 254 individual choice situations during nine observation sessions conducted over nine weeks. The results from both centers provide evidence of a strong effect of the nudge. However, the effect decreased during the follow-up study. These findings support previous research indicating that human behavior is influenced by the presence of implicit observation cues – in this case – observing eyes. However, insights into the long-term effect of implicit observation cues are still needed since the salience of the stimuli faded over time.